Preference Index of Sustainable Natural Fibers in Stone Matrix Asphalt Mixture Using Waste Marble - Singh S.; Khairandish M.I.; Razahi M.M.; Kumar R.; Chohan J.S.; Tiwary A.; Sharma S.; Li C.; Ilyas R.A.; Asyraf M.R.M.; Zakaria S.Z.S. (MDPI, 2023)
Aggregates; Asphalt mixtures; Cost effectiveness; Decision making; Fillers; Marble; Mixtures; Moisture; Natural fibers; Stability; Coir; Drain down test; EDS analysis; Marshal stability property; Marshall stability; Moisture sensitivity; Moisture sensitivity test; Rice straw fibers; SEM topography; Sensitivity tests; Sisal; Stability properties; Waste marble; Topography